2004
DOI: 10.1002/pssc.200304319
|View full text |Cite
|
Sign up to set email alerts
|

Lucky‐drift model for avalanche multiplication in amorphous semiconductors

Abstract: A new model for avalanche carrier multiplication in amorphous semiconductors is suggested. In contrary to previous considerations, the model does not employ the Shockley's lucky-electron ansatz according to which a free carrier gains the energy from electric field in a ballistic motion. We show that the majority of free carriers reaching the ionization threshold energy do so by drift, not ballistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 10 publications
2
43
0
Order By: Relevance
“…The experimental results on charge transport and effective quantum efficiency of charge photogeneration in a-Se blocking structures of HARP targets agree well with the theory of avalanche multiplication in a-Se [2,13] and previous studies [1,4,14] that showed avalanche multiplication in a-Se at electric fields in excess of 70 V/µm when drifting holes gain sufficient energy from the field to initiate impact ionization process. It should be noted that the presence of blocking layers for holes and electrons does not affect the hole transport mechanism.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The experimental results on charge transport and effective quantum efficiency of charge photogeneration in a-Se blocking structures of HARP targets agree well with the theory of avalanche multiplication in a-Se [2,13] and previous studies [1,4,14] that showed avalanche multiplication in a-Se at electric fields in excess of 70 V/µm when drifting holes gain sufficient energy from the field to initiate impact ionization process. It should be noted that the presence of blocking layers for holes and electrons does not affect the hole transport mechanism.…”
Section: Resultssupporting
confidence: 88%
“…1 Introduction Impact ionization and avalanche formation in amorphous selenium are interesting phenom-ena which have been intriguing scientists from the 1980's when these effects first were experimentally observed [1], until very recently when they first were explained in terms of the modified lucky-drift (LD) model [2,3]. During this 25 year period it has been shown experimentally that avalanche multiplication in a-Se starts at electric fields F AV ~ 70 V/µm where hot holes gain enough energy to initiate impact ionization.…”
mentioning
confidence: 99%
“…20 V/µm). This difference is attributed to intense elastic scattering due to disorder inherent to the amorphous structure [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Another approach is to try to modify theoretical models developed for crystalline semiconductors taking into account specific features of amorphous materials. The latter attempt has been recently performed by Rubel et al [15], who extended for amorphous semiconductors the LD model of Ridley taking into account elastic scattering on disorder potential inherent for amorphous materials. This scattering mechanism has not been included into the models for crystalline semiconductors.…”
Section: Introductionmentioning
confidence: 98%
“…According to the LD model of Rubel et al [15], charge carrier experiences elastic scattering on disorder potential and inelastic scattering on optical phonons while being accelerated by electric field. The particular formulation of this model sounds as follows.…”
Section: Introductionmentioning
confidence: 99%